Effect of Instagram Social Media With Guest Purchase Decisions At Ibis Style Hotel Bogor Raya - julia ratnawulan skawanti (Program Studi Hospitality dan Pariwisata, 2021)
ABSTRACK During the Covid-19 Pandemic, the government limited people's activities outside the home, causing an increase in the use of Instagram social media, especially as a means of promotion. This phenomenon is exploited by the Ibis Style Hotel Bogor Raya manager with a strategy of maximizing attractive photos and videos with only a few promotional sentences but can attract consumer interest. This study aims to determine the correlation between the use of promotions through Instagram social media and the decision to purchase guests at the Ibis Style Hotel Bogor Raya.By using quantitative research methods, using a sample of 100 people, namely hotel guests who have stayed at this hotel. Collecting data using a questionnaire that has been tested for validity and reliability. Data were analyzed using simple linear regression analysis. The data is processed using the SPSS version 25.0 applicationBased on the results of this study, it was concluded that there was a strong correlation between Instagram Social Media and purchasing decisions and proved significant with R correlation number of 0.729. Meanwhile, the percentage contribution of the product variation variable to repurchase is 53.1% and the remaining 46.9% is influenced by other variables not examined in this study.Keywords: Instagram Social Media, Purchase Decision, Ibis Style Hotel Bogor Raya